Service quality, relationship benefit and experience value in the auto repair services sector - Jinpyo Hong; Boyoung Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The purpose of this study was to analyze how service quality, relationship benefit, and experience value affect the customers' intention to maintain a long-term relationship with auto repair centers through service quality and trust. To this end, a statistical analysis was performed, based on a total of 319 survey data from customers who possess experience in using auto repair services. It was found that all factors of service quality, relationship benefits, and experience values directly influence service satisfaction and affect long-term relationship through service satisfaction. In the case of relationship benefits and experience values, however, it did not affect service trust, and the relationship benefit factor did not affect the maintenance of a long-term relationship through service trust. Consequently, it was found that in the auto repair service sector, customers consider service satisfaction more important than service trust in maintaining the long-term use relationship with a service center or sales branch. This result confirms that auto repair service has a significant influence on customers through the quality of auto repair and customer satisfaction regarding the repair results through troubleshooting, unlike general services that are affected by psychological properties such as a products' brand and attractiveness.
Keywords: 650; auto repair service; customer relationship; experience value; relationship benefit; service quality